1978
DOI: 10.1246/bcsj.51.3449
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Absorption and Fluorescence Spectra of [2.2]Anthracenophanes

Abstract: The absorption and the fluorescence spectra of four [2.2]anthracenophanes were investigated at low temperatures. A theoretical calculation of the energy levels was performed by including the charge resonance and the exciton type interactions. The fluorescence excitation polarization spectra were recorded for all absorption bands at low temperatures, the directions of the transition moment of the excimer type emission bands being estimated by the p-values and the established transition directions of anthracene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
2
16
0
2
Order By: Relevance
“…This change in vibronic lineshape is consistent with H-aggregate formation, as expected for side-by-side chromophores, and has previously been observed in cofacial anthracene dimers formed by various methods. 22,23 The change in absorption is quite different from what is observed in crystalline tetracene, where the 0-0 peak is enhanced due to J-aggregation, and a clear Davydov splitting provides a way to quantitate the intermolecular excitonic interaction. 12 The fluorescence spectrum of dimer 6 presents a broad emission band at around 535 nm, which red-shifted by about 6 nm in comparison with that of monomer 7, Fig.…”
Section: Absorption and Fluorescence Spectra In Solutionmentioning
confidence: 85%
“…This change in vibronic lineshape is consistent with H-aggregate formation, as expected for side-by-side chromophores, and has previously been observed in cofacial anthracene dimers formed by various methods. 22,23 The change in absorption is quite different from what is observed in crystalline tetracene, where the 0-0 peak is enhanced due to J-aggregation, and a clear Davydov splitting provides a way to quantitate the intermolecular excitonic interaction. 12 The fluorescence spectrum of dimer 6 presents a broad emission band at around 535 nm, which red-shifted by about 6 nm in comparison with that of monomer 7, Fig.…”
Section: Absorption and Fluorescence Spectra In Solutionmentioning
confidence: 85%
“…See text for details. d The rate constants for triplet energy transfer from 3BP* to tNP and DMN determined by eqn (5)…”
mentioning
confidence: 99%
“…It was reported that anthracene bulk crystals display distinct dual emissions from both anthracene monomers and excimers. 40,56,57 Strong excimer emission bands have also been observed in the aqueous suspension of anthracene nanoparticles. 58 In our case, the anthracene nanowires present strong monomer bands in the region of 400-550 nm.…”
Section: Resultsmentioning
confidence: 92%